Education policy and contemporary theory implications for research - Gulson, Kalervo N.; Clarke, Matthew 1964-; Bendix Petersen, Eva (London Routledge, 2015)
"This book aims to posit theory as a central component to the study of education and education policy. Providing clear, introductory entries into contemporary critical theories and their take up in education policy studies, the book offers a generative invitation to further reading, thought and exploration. Instead of prescribing how theory should be used, the contributors elaborate on a set of possibilities for researching and critiquing education policy. Education Policy and Contemporary Theory explores examples of how theoretical approaches generate a variety of questions for policy analysis, demonstrating the importance of theory as a necessary and inevitable resource for exploring and contesting various policy realms and dominant discourses. Each chapter provides a short overview of key aspects of a particular theory or perspective, followed by suggestions of methodological implications and recommended readings to extend the outlined ideas. Organized around two parts, the first section focuses on theorists while the second section looks at specific theories and concepts, with the intention that each part makes explicit the connection between theory and methodology in relation to education policy research. Each contribution is carefully written by experts in the field to introduce new scholars to theoretical concepts and policy questions, and to inspire, extend or challenge established policy researchers who may be considering working in new areas"--Provided by publisher.
Introduction : policy, theory, methodology / Kalervo N. Gulson, Matthew Clarke, and Eva Bendix Petersen -- Bourdieu and doing policy sociology in education / Shaun Rawolle and Bob Lingard -- Michel de Certeau, everyday life and cultural policy studies in education / Sue Saltmarsh -- Repeating Deleuze and Guattari : towards a politics of method in education policy studies / Sam Sellar -- Derrida : the impossibility of deconstructing educational policy enactment / Greg Vass -- Education policies as discursive formations : a Foucauldian optic / Eva Bendix Petersen -- Lacanian perspectives on education policy analysis / Matthew Clarke -- Situated, relational and practice-oriented : the actor-network theory approach / Radhika Gorur -- Thinking educational policy and management through (frictional) concepts of affects / Dorthe Staun and Justine Gr²nbaek Pors -- Assemblage theory and education policy sociology / Deborah Youdell -- Counterpublics, crisis and critique : a feminist socio-historical approach to researching policy / Jessica Gerrard -- Embodying policy studies : feminist genealogy as methodology / Wanda S. Pillow -- Governmentality : Foucault's concept for our modern political reasoning / Kaspar Villadsen -- Taking a "material turn" in education policy research? / Stephen Heimans -- Mobilities paradigm and policy research in education / Fazal Rizvi -- A narrative approach to policy analysis / Peter Bansel -- Queer theory, policy and education / Mary Lou Rasmussen and Christina Gowlett -- Thinking rhizomatically : using Deleuze in education policy contexts / Eileen Honan -- Relational space and education policy analysis / Kalervo N. Gulson.
Includes bibliographical references and index.
Keywords: Education and state -- Philosophy; Educational change -- Philosophy; Education -- Research